Cleft lip–cleft palate in Zimbabwe: Estimating the distribution of the surgical burden of disease using geographic information systems. (27th May 2014) - Tollefson, Travis T.; Shaye, David; Durbin‐Johnson, Blythe; Mehdezadeh, Omid; Mahomva, Leonard; Chidzonga, Midion
Abstract : Objectives/Hypothesis: To evaluate the prevalence and unmet need for cleft lip–cleft palate reconstructive surgery by using incidence. Our hypotheses were that the age of presentation to screening clinics will decrease between 2006 and 2012, and the geospatial distribution of cases will expand to a more rural catchment area. Study Design: Longitudinal cross‐sectional/geospatial distribution study. Methods: An online, secure database was created from intake forms for children with cleft lip–cleft palate (N = 604) in Zimbabwe (2006–2012). Univariate analysis was completed. A linear regression model was fitted to test the time trend of a child's age at the time of presentation. Unique patient addresses (n = 411) were matched. Maps presenting cleft diagnosis and presentation year were created with geographic information systems (GIS) software. Results: The median age of presentation was greater for isolated cleft palate (4.2 years, n = 106) than isolated cleft lip (1.5 years, n = 251) and cleft lip–cleft palate (2.0 years, n = 175). Cleft lip cases were mostly left sided with equal gender distribution. The overall age of presentation remained stable ( P = .83). The age of children with isolated cleft palate decreased by 0.8 years per surgical trip ( P = .01), suggesting the prevalence of unrepaired cleft palate is decreasing due to local and visiting surgeons. The catchment area extended to a less populous area, but clustered around Harare and Bulawayo. Conclusions: This study gives Zimbabwe‐specific evidence that supports reports of the persistent burden of disease requiring attention. The GIS software provided data for the primary needs assessment, which will direct communication to healthcare providers and prospective patients outside of the current catchment area. Level of Evidence: 3 Laryngoscope, 125:S1–S14, 2015